Modeling of rapid fine-grained material flows - Federico, Francesco; Cesali, Chiara (Italian journal of engineering geology and environment, 2017)
<span data-sheets-value="{"1":2,"2":"The design of appropriate mitigation measures to protect from landslides require the knowledge of the physical and mechanical processes governing their propagation. This knowledge can derive from experience, carefully verified and modeled through specific rheological models that take into account the main physical and mechanical properties referred to normal stream flows, hyperconcetrated flows, mudflows, debris flows, rock avalanches and their multiphase nature (flow like or granular). To predict the speed evolution and distance travelled by fine-grained material flows, an analytical (sliding block) model is proposed. The model takes into account (i) the (curved) geometry of the sliding surface; (ii) the mass variation due to possible erosion or deposition processes; iii) the interstitial pressures and, in particular, the evolution of the excess pore water pressures (generation, initially due to several phenomena and during the motion to the slope curvature, coupled to undrained and oedometric conditions; dissipation, due to consolidation process). The governing ordinary differential equation has been numerically solved. The role played by the main model parameters on the kinematics of rapid fine - grained material flows is evaluated through parametrical analyses and the range of their admissible values is investigated and defined. Model validations using laboratory measurements and analysing some documented cases are finally developed and carried out."}" data-sheets-userformat="{"2":15233,"3":{"1":0},"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">The design of appropriate mitigation measures to protect from landslides require the knowledge of the physical and mechanical processes governing their propagation. This knowledge can derive from experience, carefully verified and modeled through specific rheological models that take into account the main physical and mechanical properties referred to normal stream flows, hyperconcetrated flows, mudflows, debris flows, rock avalanches and their multiphase nature (flow like or granular). To predict the speed evolution and distance travelled by fine-grained material flows, an analytical (sliding block) model is proposed. The model takes into account (i) the (curved) geometry of the sliding surface; (ii) the mass variation due to possible erosion or deposition processes; iii) the interstitial pressures and, in particular, the evolution of the excess pore water pressures (generation, initially due to several phenomena and during the motion to the slope curvature, coupled to undrained and oedometric conditions; dissipation, due to consolidation process). The governing ordinary differential equation has been numerically solved. The role played by the main model parameters on the kinematics of rapid fine - grained material flows is evaluated through parametrical analyses and the range of their admissible values is investigated and defined. Model validations using laboratory measurements and analysing some documented cases are finally developed and carried out.